New frontiers in international strategy - Ricart, Joan Enric; Enright, Michael J; Ghemawat, Pankaj; Hart, Stuart L; Khanna, Tarun (Journal of International Business Studies, 2004)
This paper studies a new frontier in the understanding of International Strategy (IS). To explore it, we propose the analogy of the ecology of firms and places as a way to emphasize that the real problem is the colocation of different places with different types of firms. Locations are in fact the distinctive content of International Business Strategy. We deal with this problem with four different perspectives. First, differences across countries must be addressed with integrative frameworks able to represent the multidimensionality of 'semiglobalization', or intermediate states between total localization and total integration. Second, differences in the development of intermediary markets in a particular place influence firm positioning and industry structure in that place, but their impact also crosses different places, and it is endogenous to the ecology of places and firms in a systemic, integrative way that makes simplifications extremely risky in the design of competitive strategy in an international context. Third, places, firms, and strategies form a complex ecology that can be studied with a framework focused in understanding the geography-strategy link that incorporates different levels of analysis, new economic actors, and a set of primitives. Finally, firms around the ecology of places face the challenge of developing strategies and business models to serve the majority of humanity today excluded from world trade. It is a fundamentally different way to think about the ecology of places and firms. Overall, we present an intriguing New Frontier, with the capacity to impact both research and practice in the field of international strategy, based in understanding the interplay among firms and places.